Sensorial profile of Apis mellifera’s honeys produced by familiar farmers in Iguape Bay, Bahia, Brazil - Silva, Samira Maria Peixoto Cavalcante (2014)
Sensory proprieties of the honeys are amongst the main parameters for its quality determination, with sensory analysis working as a tool for measurement and quantification of the product characteristics by human senses. Sensorial quality control considers attributes as color, scent, flavor and consistency. These attributes are always interlinked and depend on volatile substances that are related to the original scents of flowers where the nectar was collected. Scent and flavor are directly related to honey’s color and mainly depend on its floral origin. This work had the objective to discern the sensory profiles of Apis mellifera honey produced by familiar farmers from the Iguape bay, in Bahia, Brazil. A total of 11 A. mellifera honey samples were obtained from beekeepers and processed in the Laboratory of the Nucleus for Insect Studies (INSECTA) of the Centro de Ciências Agrárias, Ambientais e Biológicas at Universidade Federal do Recôncavo da Bahia in Cruz das Almas, Bahia. The sensorial analysis performed by the 50 consumers, revealed that the acceptance of honey was higher in the Caonge’s community and significantly different from the obtained in the Engenho Vitória’s community.